Development of a guinea pig cutaneous radiation injury model using low penetrating X-rays. (2nd August 2016) - Rodgers, Kathleen E.; Tan, Alick; Kim, Lila; Espinoza, Theresa; Meeks, Christopher; Johnston, William; Maulhardt, Holly; Donald, Melissa; Hill, Colin; diZerega, Gere S.
Abstract: Purpose: A guinea pig skin model was developed to determine the dose-dependent response to soft X-ray radiation into the dermis. Materials and methods: X-ray exposure (50 kVp) was defined to a 4.0 × 4.0 cm area on the lateral surface of a guinea pig using lead shielding. Guinea pigs were exposed to a single fraction of X-ray irradiation ranging from 25–79 Gy via an XRAD320ix Biological Irradiator with the collimator removed. Gross skin changes were measured using clinical assessments defined by the Kumar scale. Skin contracture was assessed, as well as histological evaluations. Results: Loss of dermal integrity was shown after a single dose of soft X-ray radiation at or above 32 Gy with the central 2.0 × 2.0 cm of the exposed site being the most affected. Hallmarks of the skin injury included moist desquamation, ulceration and wound contracture, as well as alterations in epithelium, dermis, muscle and adipose. Changes in the skin were time- and radiation dose-dependent. Full-thickness injury occurred without animal mortality or gross changes in the underlying organs. Conclusions: The guinea pig is an appropriate small animal model for the short-term screening of countermeasures for cutaneous radiation injury (CRI).